HISTORICAL NARRATIVES ABOUT THE MONGOLS IN LIGHT OF THE BOOK "COUNTRIES OF THE EASTERN CALIPHATE" OF THE ORIENTALIST GUY LE STRANGE - Dr. Suaad Hadi Hassan Al-Taai (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Guy Le Strange is a British orientalist, born in 1271 AH/1854AD, from a noble family in the Northern Province of Norfolk in Eastern England, and was mentioned in the county of Hunstanton. He traveled to several countries to study and teach. He mastered several languages, especially Persian and Spanish. He was interested in studying the Islamic East and classed In addition to his translation of a number of Persian books, he obtained a master's degree in 1332 AH/1913 CE from the University of Cambridge, specializing in the study of the geographical history of Arabia and Persia, and practiced the profession of teaching there, he died in London in the year 1352 AH/1933 CE. The importance of the topic lies in the fact that his book The Countries of the Eastern Caliphate is one of his most important books, and although it included extensive geographical information on the Islamic East, it contained important historical narratives, the most important of which was related to the history of the Mongols and the most important military campaigns they launched against the Islamic countries and in different historical periods. The study came out with important results that clarify the devastation and destruction committed by the Mongols in the Islamic countries that they controlled, and refer to the most important urban reforms carried out by the Ilkhan Ghazan, and the construction of the city of Sultana during the reign of the Ilkhan Oligaito.